Turkey and Iran approaches to engagement in the Middle East - Keyman, Emin Fuat (Emirates lecture series, 2013)
"The fact that Turkey will always maintain its Western identity means that a new status quo in Turkish-Iranian affairs will never develop until Iran confronts and settles its domestic discontent. Iran is at a fundamental crossroads today. The foreign policy decisions that Tehran will take is going to have irrevocable ramifications for the region and its partners. If the Iranian regime chooses to follow a more cooperative foreign and regional policy, the stability and prosperity blanket that Turkey has weaved will create a conducive environment for Iran to merge its capacity with others and work towards the common welfare of the region. However, if Tehran opts for nation building and sectarian policies, the regime will risk the deterioration of its constructive relations with steadfast patrons and partners like Turkey."--Summary.